MBKM Scientific Research: Experience in Nano Aging Asphalt Research Program at UMS: Riset Keilmuan MBKM: Pengalaman Mengikuti Program Riset Aspal Nano Aging di UMS - Rudyanto, Monica; Riyanto, Agus; Rizana, Rama; Sunarjono, Sri (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
The Merdeka Learning Campus Merdeka Program is an application of collaborative learning, which aims to strive for graduate abilities, both soft skills and hard skills, so that graduates are ready and in accordance with the demands of the times, planning graduates as future leaders with character. This research is part of the first MBKM Research in the Civil Engineering Study Program at Universitas Muhammadiyah Surakarta, which involves several parties outside the scope of the Civil Engineering discipline. The purpose of this research is to share the experience of the MBKM research program, as well as to find out the results of nano aging asphalt. The method used is laboratory experiments in the form of testing the physical properties of asphalt (Penetration, Softening Point, Specific Weight, Ductility), and supporting testing results (SEM-EDX and FTIR). The results showed that the MBKM research program demonstrated the continuity between engineering sciences, as well as improved the quality of nano aging asphalt.